Biofilm formation and effect of disinfectant onthe isolates obtained from aquatic ecosystem (BioMedical Research in Microbiology (BMR Microbiology) (ISSN: 2349-4603), 2024)
Aeromonas spp. are common aquatic micro-organisms that occur in seawater, irrigation water, river water, brackish water, fresh water, ground water, spring water, industrial and domestic waste water. Aeromonas spp. is associated gastrointestinal diseases, mainly diarrhea, septicemia, wound infections and diseases of amphibians, reptiles, frog, fish etc. Every month water samples were collected from well (village pal), river (Tapti river), tap(Surat Municipal Cooperation), mineral (Aquafina), sea (brackish) and swimming pool (chlorinated) of Surat city during year 2009 to 2010 and analyzed microbiologically. Isolates like Aeromonas hydrophila, Aeromonassalmonicida, Aeromonas salmonicida sub spp. smithia, Aeromonas salmonicida sub spp. masoucida, Aeromonas schubertii, Aeromonas veronii, Aeromonas media and Aeromonas caviae were obtained from the water samples and were further tested for their Biofilm formation and effect of disinfectant was checked on the produced Biofilm. As Aeromonas species are one of the Biofilm producing organism, the Biofilm production test was carried out by using polycarbonated plastic/PVC and Glass coupons deeped in three different containers like copper, steel and clay. Weight of the polycarbonated plastic coupons and glass coupons were noted and at the interval of 15 days and 30 days, increase in weight of the plates and coupons showed Biofilm formation. In water distribution system these organisms produce the Biofilm and so to remove it disinfectant treatment is used. Disinfectant treatment using (chlorine tablets) containing sodium dichloro isocyanurate, having 10 ppm of chlorine commercially available to disinfect drinking water. Serial plate count was done using M-Aeromonas selective media to get specific number of Aeromonas species. The hanging glass coupons were removed at timeinterval of 30min, 60min, 90min (with treatment of disinfection) and 0 min (without disinfection). The coupons were stain by using fluorescent dye Acridine orange to get number of viable and non viable cells forming Biofilm. We can also conclude that the Biofilm produced by them in a water distribution system i.e. pipe lines or domestic vessels can be controlled easily by disinfectants within an hour.